1987
DOI: 10.1037/0278-6133.6.5.399
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and effectiveness of school-based relaxation in lowering blood pressure.

Abstract: Progressive muscle relaxation (PMR) is a broadly useful anxiety reduction technique that has been found to lower blood pressure (BP) in essential hypertension. The present investigation is the first to evaluate the feasibility and efficacy of wide-scale PMR instruction as a public health promotion strategy aimed at adolescents. Students (N = 1,400) in Grades 9 and 10 at two large Baltimore City public high schools underwent BP screening; those with BP persistently above the 85th percentile were randomly assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Relaxation training combined with increased physical activity for four months failed to yield any BP differences in community-home boys compared to a control group (36). A daily progressive muscle relaxation program conducted for 4 months at school in teenagers with high normal BP showed a 5.3 mm Hg greater decrease in their SBP compared with a waiting list control condition (12). Findings in AA adolescents with high normal BP indicated that TM lowered resting SBP/DBP by 7.4/4.7 mm Hg after 2 months of intervention and daytime ambulatory SBP/DBP by 4.3/4.0 mm Hg after 4 months of intervention compared to health education controls (13,19).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Relaxation training combined with increased physical activity for four months failed to yield any BP differences in community-home boys compared to a control group (36). A daily progressive muscle relaxation program conducted for 4 months at school in teenagers with high normal BP showed a 5.3 mm Hg greater decrease in their SBP compared with a waiting list control condition (12). Findings in AA adolescents with high normal BP indicated that TM lowered resting SBP/DBP by 7.4/4.7 mm Hg after 2 months of intervention and daytime ambulatory SBP/DBP by 4.3/4.0 mm Hg after 4 months of intervention compared to health education controls (13,19).…”
Section: Discussionmentioning
confidence: 60%
“…To date, few studies have evaluated stress reduction interventions on BP in prehypertensive youth, but findings have been encouraging. Progressive muscle relaxation (PMR) training was shown to reduce systolic BP (SBP) relative to controls after 3 months (Ϫ7.2 vs. Ϫ1.9 mm Hg) in predominantly white adolescents (12). Transcendental Meditation™ (TM) reduced daytime SBP and diastolic BP (DBP) at 2-month and 4-month evaluations and at 4-month follow-ups (average change across evaluations: Ϫ3.9 vs. Ϫ0.9 mm Hg for SBP; Ϫ2.4 vs. Ϫ0.1 mm Hg for DBP) compared to a health education control group in AA adolescents (13).…”
Section: Introductionmentioning
confidence: 99%
“…Between sessions, the patients used temperature-sensitive "Biodots" (Biodot International, Inc., Indianapolis, Indiana) as a means for temperature feedback and were Psychosomatic Medicine 54:87-101 (1992) 89 instructed to increase finger temperature during relaxation sessions [c.f. (5)]. A "self control model," was used as a rationale for the biofeedback treatment.…”
Section: Treatmentsmentioning
confidence: 99%
“…For example, one approach to meditation and relaxation is a traditional system of movement meditation based on yoga-type principles (Manocha et al, 2002), which incorporate muscle relaxation, breath control, and mental focus on particular body movements and postures. Although not a meditation technique, progressive muscle relaxation training is an approach that integrates some similar principles, including relaxed posture, controlled breathing, and attention to feelings and sensations that accompany the relaxation phase, while incorporating the systematic innervation and relaxation of certain muscle groups (Ewart, 1987;Schneider et al, 1995).…”
Section: Meditation and Relaxation Trainingmentioning
confidence: 99%